Leviathan With Selected Variants from the Latin Edition Of 1668 : With Selected Variants from the Latin Edition Of 1668. - Hobbes, Thomas, 1588-1679.; Curley, E. M. (Edwin M.), 1937- (Indianapolis : Hackett Pub. Co., 1994)
Designed to meet the needs of both student and scholar, this edition of Leviathan offers a brilliant introduction by Edwin Curley, modernized spelling and punctuation of the text, and the inclusion, along with historical and interpretive notes, of the most significant variants between the English version of 1651 and the Latin version of 1668. A glossary of seventeenth-century English terms, and indexes of persons, subjects, and scriptural passages help make this the most thoughtfully conceived edition of Leviathan available. "A scholar's edition at a student price!"--Harvey Mansfield, Harvard.
Part I: Of man -- Part II: Of commonwealth -- Part III: Of a Christian commonwealth -- Part IV: Of the kingdom of darkness.
Includes bibliographical references and indexes.
Keywords: Political science -- Early works to 1800.; State, The; Political science; State, The; Politieke filosofie; Hobbes, thomas; Filosofia moderna; Ciencia politica; Electronic books; Early works